Chinas Abgang von der Weltbühne (PROKLA. Journal of Critical Social Science, 2010)
After having been one of the world’s most prosperous countries China fell back and into disarray in the course of the nineteenth and twentieth century. The causes of this process are mostly interior, but exacerbated by the assault of Western and Japanese imperialism. It is before this background that the present regime is to be looked upon.